2021
DOI: 10.1097/rli.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Chest Radiography Reporting Accuracy

Abstract: ObjectivesChest radiographs (CXRs) are commonly performed in emergency units (EUs), but the interpretation requires radiology experience. We developed an artificial intelligence (AI) system (precommercial) that aims to mimic board-certified radiologists' (BCRs') performance and can therefore support non–radiology residents (NRRs) in clinical settings lacking 24/7 radiology coverage. We validated by quantifying the clinical value of our AI system for radiology residents (RRs) and EU-experienced NRRs in a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Generally, older and more experienced physicians were more skeptical, were less likely to use AI results, and saw fewer benefits. This might be because experienced readers often show less pronounced improvement with AI support, but in numerous studies, their improvement also showed to be significant 5,12–14 …”
Section: Discussionmentioning
confidence: 99%
“…Generally, older and more experienced physicians were more skeptical, were less likely to use AI results, and saw fewer benefits. This might be because experienced readers often show less pronounced improvement with AI support, but in numerous studies, their improvement also showed to be significant 5,12–14 …”
Section: Discussionmentioning
confidence: 99%
“…ROC curve). As one of the main goals of a CAD system, is to reduce the variability among readers in an assisted setting 12,13 , any improvement of the CAD system performance outside the effective interval, will not impact the reader's performance in an assisted setting. Here, the region of interest (ROI) is shown where the performance improvement is most desired.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we first study the improvements from the AUCReshaping function on a dataset of Chest X-Rays (CXRs). With the acquisition of millions of CXR images, the ability to filter out normal images with high confidence saves radiologists, the burden of parsing hundreds of images daily 12,13,18 . This allows them to focus on critical patients, dramatically speeding up the diagnostic process, which is especially critical in pandemic-like situations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, artificial intelligence (AI) has shown high potential in mimicking health care specialists' performance in medical image interpretation. [16][17][18][19][20] Nevertheless, and despite over 50 years of research in conventional computer-aided diagnosis, there is still a paucity of algorithms for catheter evaluation in chest radiography, especially with regard to CVC evaluation. 11 Here, we present the development and validation of an AI algorithm that automatically assesses the positioning of CVCs and TTs in CXRs relative to anatomical landmarks, which is supposed to prospectively become integrated in a more extensive, CXR-analyzing software package.…”
mentioning
confidence: 99%
“…Nevertheless, and despite over 50 years of research in conventional computer-aided diagnosis, there is still a paucity of algorithms for catheter evaluation in chest radiography, especially with regard to CVC evaluation 11 . Here, we present the development and validation of an AI algorithm that automatically assesses the positioning of CVCs and TTs in CXRs relative to anatomical landmarks, which is supposed to prospectively become integrated in a more extensive, CXR-analyzing software package 16,21,22 . The algorithm uses a convolutional neural network (CNN) approach and has been trained on nonpublicly available, annotated CXRs from different clinical sites.…”
mentioning
confidence: 99%